Efficacy and safety of Chinese herbal medicine for mammary nodules: A systematic review and meta-analysis - Shuo Zhang; Xin Zhang; Zhen-Lin Chen; Pu Zhang; Miao Wang; Hong-Yan Wang; Jing-Ming Zhang (Traditional Medicine and Modern Medicine, 2021)
Background: Chinese herbal medicine (CHM) is often used in China to treat patients with mammary nodules (MMND), and treating them by CHM can not only achieve good efficacy, but also reduce adverse reactions in clinic. However, the efficacy of CHM in the treatment of MMND has not been systematically assessed right now. Methods: From the establishment of 11 electronic databases to February 1, 2022, a comprehensive literature search was conducted to evaluate the efficacy and safety of CHM in the treatment of MMND. Relevant trials were screened in NoteExpress, and the risks of bias were assessed with Cochrane Collaboration’s tool. Results: This study included 22 randomized controlled trials involving 3839 participants. Meta-analysis revealed that CHM had a significant clinical effect in treating MMND. Compared with chemical drugs, CHM had certain advantages in alleviating the size, range, hardness and pain of the lump, decreasing the TCM syndrome score and reducing the packed cell volume and whole blood viscosity. And it could obviously reduce the occurrence of adverse reactions. In combination with chemical drugs, CHM could significantly improve the level of sex hormone secretion and ultrasound indicators. Ru-pi-xiao was the most commonly used formula for the treatment of MMND, and Bupleuri Radix was the most frequently used single Chinese herb. Conclusion: CHM had certain advantages in treating MMND without obvious adverse reactions. However, due to the poor methodological quality of the included trials, well-designed, long-term follow-up randomized controlled trials will be required in future to provide strong clinical evidence for the CHM treatment of MMND. (PROSPERO No. CRD42020170939.)